A 2-d orbital period for a redback millisecond pulsar candidate in the globular cluster NGC 6397. Issue 1 (11th March 2021) - Marcano, Manuel Pichardo; Rivera Sandoval, Liliana E; Maccarone, Thomas J; Zhao, Yue; Heinke, Craig O
ABSTRACT: We report optical modulation of the companion to the X-ray source U18 in the globular cluster NGC 6397. U18, with combined evidence from radio and X-ray measurements, is a strong candidate as the second redback in this cluster, initially missed in pulsar searches. This object is a bright variable star with an anomalous red colour and optical variability (∼0.2 mag in amplitude) with a periodicity ∼1.96 d that can be interpreted as the orbital period. This value corresponds to the longest orbital period for known redback candidates and confirmed systems in Galactic globular clusters and one of the few with a period longer than 1 d.